1998
DOI: 10.1007/pl00004657
|View full text |Cite
|
Sign up to set email alerts
|

On the homology of configuration spaces $ C((M,M_0) \times R^n; X)$

Abstract: The homology with coefficients in a field of the configuration spaces C(M × R n , M 0 × R n ; X) for n ≥ 1 and general space X is determined in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
(36 reference statements)
0
14
0
Order By: Relevance
“…In our previous study, the crystallinity degree of PLLA obtained from heating curve is very low. 33 Therefore, the incorporation of ABS particles cannot promote the melt crystallization of PLLA.…”
Section: Ftir Spectra Of Plla and Plla/abs Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, the crystallinity degree of PLLA obtained from heating curve is very low. 33 Therefore, the incorporation of ABS particles cannot promote the melt crystallization of PLLA.…”
Section: Ftir Spectra Of Plla and Plla/abs Blendsmentioning
confidence: 99%
“…33 The results showed that PLLA with a small amount of modifier could achieve the enhancement of desired mechanical properties because the modifiers in the matrix formed very fine dispersions. [32][33][34] ABS core shell copolymer is synthesized by PB seed emulsion polymerization of styrene and acrylonitrile monomer solution, which is very good toughening modifier for ABS resin to efficiently improve the interfacial interaction between PB rubber phase and ABS resin matrix. 12 The polarity of PSAN shell layer could be adjusted by controlling the composition of polystyrene and polyacrylonitrile.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental 2,4-Dichlorophenoxyacetic acid was synthesized according to the literature (Wu et al, 1996). Cadmium dinitrate tetrahydrate (6.16 g, 20 mmol) and 2,4-dichlorophenoxyacetic acid (4.42 g, 20 mmol) were dissolved in a 1:2 ethanol/water mixture.…”
mentioning
confidence: 99%
“…This assumption is supported by the recent demonstration of an antiapoptotic role of a longer splicing variant of p22/ PRG1-termed IEX-1L-that protects from TNF-α and Fas-mediated apoptosis in a variety of cells. 12 However, the detailed cellular function of both isoforms of p22/ PRG1/IEX-1 in this context is unknown.…”
Section: Discussionmentioning
confidence: 99%